Improvements in GRACE-based terrestrial water storage anomalies for groundwater depletion and ecohydrological analyses - Ukasha, Muhammad, author; Niemann, Jeffrey D., advisor; Grigg, Neil S., committee member; Bailey, Ryan T., committee member; Ronayne, Michael J., committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.
Keywords: GRACE; rescaling; downscaling; TWSA; hydroclimatology